ANALISIS SWOT TERHADAP STRATEGI OPTIMALISASI MENARA BERSAMA TELEKOMUNIKASI: (STUDI PADA PT. DAYAMITRA TELEKOMUNIKASI Tbk REGIONAL JATENG & DIY) - Oky Sjahrul Syah; Endang Tjahjaningsih (Pusat Riset dan Inovasi Nasional, 2025)
Analyzing the optimization strategy for telecommunications towers as tower sharing using a SWOT analysis to support decision-making and increase company revenue. The results show that optimizing telecommunications towers as tower sharing can improve network coverage, service quality, maximize tower utilization, and efficiency, thereby increasing company revenue, improving service quality, and providing more competitive pricing.